Challenges and business sustainability of Jolly Banana Farm - Falgui, Rommel Thomas M.; Gomez, Aurelia Luzviminda V.; Bangcaya, Exegesis Jedidiah E. (2018)
This paper discusses the challenges and business sustainability of Jolly Banana Farm in the Philippines with a direct international market destination in Shanghai, China. The farm is located in Brgy. Conel, General Santos City and has Cavendish banana as its primary produce as of now. The farm is under a sole proprietorship which spans to 12 hectares and has a competitive irrigation and fertilization program which enables it to be highly efficient when it comes to Class A produce. It?s efficiency as of now on its second year of operations is 1.7 BSR (box-stem ratio) which is much higher than the industry standards of 1.3. Jolly Banana Farm started with a working capital of PhP 2,500,000.00 and was supported by a loan of about PhP10,000,000.00. it had its first harvest and exportation last July 2017 which recorded a net profit of about PhP1.4 million. Despite this high productivity rate, Jolly Banana Farm has to maximize its market to fully expedite its demand. Moreover, it also has to address several issues that young corporations have during its first five years of operation like variable market and market price, financial recording and analyses, income and losses, etc. to identify various alternative strategies suited for Jolly Banana Farm, the author used Fred R. David?s model which utilized several matrices such as the SWOT matrix, SPACE matrix and QSPM matrix. Out of these matrices, the derived alternative strategies were Market Development, Market Penetration and Product Development. It was also found out that the biggest strength of the company is its direct access to the international market. There were several opportunities that the company may expedite like the availability of one of the biggest distributor of agricultural goods in China. On the other hand, the weakest links the company has are the absence of an R&D to develop and improve the product, and the non-contract relationship of between Jolly Banana Farm and ?The Good Farmer?. Moreover, according to the SPACE matrix, Jolly Banana Farm is doing well and has to invest in the market and on its product given that it has an aggressive profile. Finally, to implement these strategies, a 5-year plan was designed. There will be three programs that will increase production and the supply rate, and at the same time, the market share of Jolly Banana Farm. This include the: a) twinning program where banana two followers are fed and given nutrition at the same time; b) farm expansion; c) middle farm for small-scale grower who don?t have direct access to the direct market. These activities will surely incur cost. Thus, Jolly Banana Farm will have to make another loan of the Land Bank of the Philippines under the same loan program. Agri-Financing, amounting to PhP12,500,000.00 at 7.5% annual interest.
Thesis (Master in Management) -- University of the Philippines Mindanao, April 2018